P272 Epidemiology of idiopathic pulmonary fibrosis in the uk: findings from the british lung foundation's 'respiratory health of the nation' project. (15th November 2016) - Snell, N; Strachan, D; Hubbard, R; Gibson, J; Maher, T; Jarrold, I
Abstract : Introduction and objectives: The last comprehensive survey of UK respiratory disease epidemiology was the British Thoracic Society's 2006 Burden of Lung Disease report. We performed an analysis covering 2004–2012. Findings pertaining to IPF are presented here. Methods: Prevalence and incidence rates were estimated from a primary care database (the Health Intelligence Network) representing ∼5 per cent of the population, using a broad range of primary care codes considered to encompass the IPF definition. Mortality figures were derived from official government statistics. For international mortality comparisons and numbers of hospital admissions/inpatient bed-days we used WHO data. Results: An estimated 32, 500 people in the UK live with IPF, a prevalence rate of about 50/100, 000. This is more than double NICE's 2015 estimate of 15–25 per 100, 000. There are around 6, 000 new cases diagnosed/year, greater than previous estimates of around 5, 000. Overall, 5, 300 people/year die from IPF, slightly more than the previous commonly accepted estimate of 5, 000. There are nearly 9, 000 admissions/year for IPF, accounting for around 1.3% of all admissions due to lung disease and 1.4% of all hospital bed days, despite IPF affecting less than 0.25% of people who have had a lung disease diagnosis. IPF is 50% more common in men, and killed 60% more men than women from 2008–2012. In this period 13, 974 men and 8, 624 women died from IPF, broadly in line with previous estimates. Incidence increases with age, around 85% of diagnoses being made in people aged over 70. Prevalence is highest in Northern Ireland, north-west England, Scotland and Wales. IPF is least common in London. Incidence is not influenced by measures of deprivation. Conclusions: Although rare, IPF is considerably more common than previously recognised and represents a small but significant burden on NHS hospital services.